2022
DOI: 10.1590/0100-29452022849
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, purification and characterization of invertase from Candida guilliermondii isolated from peach solid wastes

Abstract: The best conditions for in vitro sucrose hydrolysis based on invertase from Candida guilliermondii (ICg) were studied and the kinetic parameters KM,Vmax, and thermal stability of ICg were determined. Candida guilliermondii (Cg) yeast isolated and lyophilized from peach solid wastes was identified using the API 20C AUX method. Subsequently, the Cg was submitted to an autolysis process using NaHCO3 at 200 mM under 200 rpm stirring and 40 °C for 24 h. The enzyme extracts obtained were recovered through precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Overall, fungal β-D-fructofuranosidases have an optimal pH in the range of 5.0–6.5 while those from bacteria are in a range from 6.0 to 8.0. BbFFase9, with an optimal pH of 6.5, was similar to that of other bifidobacterial β-fructofuranosidases [ 3 , 5 ], but lower than that of many other bacterial β-fructofuranosidases [ [22] , [23] , [24] ], and higher than most fungal β-D-fructofuranosidases from Candida guilliermondii [ 10 ], Gongronella sp. w5 [ 25 ] and Aspergillus spp.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Overall, fungal β-D-fructofuranosidases have an optimal pH in the range of 5.0–6.5 while those from bacteria are in a range from 6.0 to 8.0. BbFFase9, with an optimal pH of 6.5, was similar to that of other bifidobacterial β-fructofuranosidases [ 3 , 5 ], but lower than that of many other bacterial β-fructofuranosidases [ [22] , [23] , [24] ], and higher than most fungal β-D-fructofuranosidases from Candida guilliermondii [ 10 ], Gongronella sp. w5 [ 25 ] and Aspergillus spp.…”
Section: Resultsmentioning
confidence: 98%
“…infantis [ 9 ]. Other aspects of these β-D-fructofuranosidases have also been studied, including enzyme production [ 6 ], enzyme purification [ 9 ], biochemical characterization [ 7 , 10 ] and the cloning and expression of β- d -fructofuranosidase genes [ 8 ]. These preliminary exploratory studies have shown this type of β- d -fructofuranosidase has good prospects for use in various industries, including the production of invert sugar.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] along with a few other microorganisms, such as Candida spp. [ 26 ], Cunninghamella echinulata [ 27 ], and Microbacterium trichothecenolyticum [ 3 ]. Given the urgent demand for industrial production, the exploration of superior microbial resources for enzyme production remains a popular topic in enzyme research.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 ], Bacillus spp. [ 15 , 16 , 17 ], Candida guilliermondii [ 18 ], Microbacterium trichothecenolyticum [ 19 ], and Cunninghamella echinulata [ 20 ], exhibit sufficient ability to produce β-D-fructofuranosidase. Among them, Aspergillus spp.…”
Section: Resultsmentioning
confidence: 99%